INKONSISTENSI DIPLOMASI ISLAM DI DALAM LIGA ARAB - Yulia Rimapradesi; Surwandono Surwandono (Dauliyah: Journal of Islam and International Affairs, 2022)
The Arab League is an organization that articulates Islamic messages and norms in the practice of International Relations. The central idea of the Arab League is reflected in the norms to carry out the politics of liberation of Palestima as a community whose existence must be fought for. However, in the context of conflict in the Middle East region especially post Arab Springs, the behavior and policies of the Arab League have received a very sharp spotlight in the practice of International Relations. This article explains the inconsistent practice of Islamic diplomacy in the case of intervention in Libya and Syria, which then results in a decline in the quality of humanity in Syria and Libya. This article finds that the Arab League has violated the norms of Islamic diplomacy such as muamalah bil misli in the form of double standard practices, and the norm of wafa 'bil ahdi in the form of inconsistencies in carrying out basic organizational norms.